2018
DOI: 10.1093/hmg/ddy433
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the dystonia geneThap1leads to transcriptional deficits that converge on common pathogenic pathways in dystonic syndromes

Abstract: Dystonia is a movement disorder characterized by involuntary and repetitive co-contractions of agonist and antagonist muscles. Dystonia 6 (DYT6) is an autosomal dominant dystonia caused by loss-of-function mutations in the zinc finger transcription factor THAP1. We have generated Thap1 knockout mice with a view to understanding its transcriptional role. While germ-line deletion of Thap1 is embryonic lethal, mice lacking one Thap1 allele-which in principle should recapitulate the haploinsufficiency of the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 81 publications
2
50
1
Order By: Relevance
“…Another study found that THAP1 is required for the timing of myelination initiation in oligodendrocyte during CNS maturation in mouse (Yellajoshyula et al 2017). More recently, Frederick et al (2019) transmission, cytoskeleton, gliosis, and dopamine signaling. However, to our knowledge, the role of THAP1 in regulating gene expression in human neuronal cells is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that THAP1 is required for the timing of myelination initiation in oligodendrocyte during CNS maturation in mouse (Yellajoshyula et al 2017). More recently, Frederick et al (2019) transmission, cytoskeleton, gliosis, and dopamine signaling. However, to our knowledge, the role of THAP1 in regulating gene expression in human neuronal cells is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The THAP1 protein belongs to the family of zinc fingercontaining transcription factor and functions as a transcription factor (Roussigne et al 2003;Bessière et al 2008). Recently, comprehensive transcriptome analysis of mouse model for DYT6 dystonia showed altered expression of genes involved in many different pathways (Yellajoshyula et al 2017;Zakirova et al 2018;Frederick et al 2019). However, the transcriptional functions of THAP1 in human neuronal cells are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The degeneration of matrix neurons in later disease stages leads to MSA-like parkinsonism due to reduced postsynaptic dopamine receptor density. S striosomes, M matrix, SNc substantia nigra pars compacta, D1 dopamine D1 receptor, D2 dopamine D2 receptor, GABA gamma aminobutyric acid, MSA multiple system atrophy knockout (Zhang et al 2011;Vanni et al 2015) and THAP1 knock-in (Ruiz et al 2015) as well as knock-out mouse models (Frederick et al 2019).…”
Section: The Role Of the Cerebellummentioning
confidence: 99%
“…Dystonia 6, a subtype of primary monogenic torsion dystonia, is a movement disorder involving dysfunctions of the central nervous system and characterized by involuntary muscle contractions. It is caused by a variety of THAP1 mutations (90 to date) spread over the entire THAP1 gene [23][24][25]52,53]. Studies are conflicting as to the effect of the THAP1 F81L mutation on THAP1 DNA binding-with either little, if any [54], partial [51], or apparently complete [55] loss of THAP1-DNA binding described, suggesting that the effect of the mutation on DNA binding is sensitive to the conditions for analysis.…”
Section: Linking the Thap11 F80l Mutation With Human Diseasementioning
confidence: 99%